Optimization of cleaning-in-place (CIP) procedure of milk fouling deposit using different cleaning parameters - Asming, Nur Aziemah Adilah; Ab Aziz, Norashikin; Mohd Thani, Nurfatimah; Khalid, Nurul Izzah (Hibiscus Publisher Enterprise, 2024)
Cleaning-in-place (CIP) is a critical process across various industries, particularly in the food industry, where maintaining sanitation without equipment disassembly is imperative. However, challenges such as cross-contamination and escalating sanitation costs may arise when protocols are not diligently followed. This research focuses on optimizing the CIP techniques to mitigate milk fouling deposits in the dairy industry by strategically manipulating cleaning parameters. A physical model using raw milk to simulate industrial scenarios was prepared, followed by laboratory-scale sanitation experiments. Here, the Box–Behnken experimental design was employed to determine the optimal cleaning parameters for the detergent cycle step. The investigation evaluated the effects of temperatures (30°C, 50°C, 70°C), mixing ratio of cleaning solution (water: cleaning detergent) (0:50, 1:50, 1:100), and fluid velocities (0.5 m/s, 1.0 m/s, 1.5 m/s) on the removal of milk fouling deposits. The cleaning solution used in this work falls under the anionic chemical family and was used to clean equipment in the food industry. The cleaning time for the removal of milk fouling deposits was measured during the sanitation experiments. The optimal conditions were found at 60°C, detergent ratio 1:83, and fluid velocity 1.5 m/s, reducing cleaning time to 11.58 minutes for 100% removal from stainless-steel surfaces. These findings challenge the commonly practiced 30-minute detergent cycle step, highlighting potential time and cost savings. The study highlights temperature and fluid velocity's vital role in enhancing CIP efficiency, providing practical insights for dairy industry improvements.